Nuestras momias, nuestra historia : entre las memorias y el patrimonio funerario de San Bernardo, Cundinamarca (2018)
San Bernardo is a rural town of Cundinamarca where some deceased relatives are mummified by natural causes and have become a funerary heritage of the region. This research asks about the processes and agents that construct these mummies as patrimonial elements, and also how their different understandings are articulated or come into tension as they are bodies of relatives who are now exhibited inside a museum. Hence, I explored the social universe embodied by the mummies through their materiality, the memories of their relatives, the catholic religion, the official speech of the museum and the perceptions of the visitors. The main objective was to account for the meanings of the mummies given by the relatives and contrast them with the collective memory discourse formulated by the museum. Thus, the museum is understood as an institution that presents and represents the mummies in a way that grants them a specific value...